Prevalence of arterial hypertension in Cushing's syndrome. - Rodrigues, D (1997)
To determine the prevalence of hypertension (HT) in patients with Cushing's syndrome.We studied 23 patients with Cushing's syndrome, 17 women (mean +/- SD age = 42.8 +/- 15.6 years) and 6 men (mean +/- SD age = 34.8 +/- 10.2 years). The etiologies were: 16-Cushing's disease, 3-suprarenal adenoma, 2-suprarenal carcinoma and 2-iatrogenic. Blood pressure (BP) was measured at least three times and we consider hypertension when systolic BP > or = 140 mmHg and/or diastolic BP > or = 90 mmHg.The prevalence of HT, at diagnosis, was 73.9% (64.7% in women and 100% in men) and the mean BP was 163 +/- 25/100 +/- 16 mmHg (158 +/- 26/97 +/- 15 mmHg in women and 182 +/- 5/114 +/- 10 mmHg in men). From the 16 patients with Cushing's disease, 13 (81%) had HT; all the patients (n = 3) with suprarenal adenoma had HT; none with suprarenal carcinoma (n = 2) had HT and only 1 of the 2 patients with iatrogenic Cushing's syndrome had HT. After treatment, 14 patients entered remission, 6 persisted with active disease and 1 was missed during the follow-up. In the group of patients that entered remission, the prevalence of HT at diagnosis was 78.5% (n = 11), 57.1% (n = 8) being after treatment.In this study, we found a high prevalence of HT at diagnosis (73.9%). After treatment and in the patients that entered remission, the prevalence of HT remained high (78.5% vs 57.1%). The high prevalence of HT in Cushing's syndrome, suggests its importance as a morbidity factor and also as an important diagnostic indicator, when present.